2021
DOI: 10.1002/anie.202012909
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Enabled Enantioconvergent Synthesis of α‐Amino Acid Derivatives via Synergistic Brønsted Acid/Photoredox Catalysis

Abstract: An unprecedented radical cross‐coupling reaction was achieved between glycine esters and racemic α‐bromoketones catalyzed by synergistic Brønsted acid/photoredox catalysis, thus serving as an efficient platform for the synthesis of highly valuable enantioenriched unnatural α‐amino acid derivatives. This dual catalysis provides a powerful capability to control the reactive radical intermediate and iminium ion, thereby enabling enantioconvergent bond‐formation in a highly stereochemical manner. An array of valua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 54 publications
(1 reference statement)
1
40
0
Order By: Relevance
“…Enantiopure β‐branched α‐amino acids are very important molecules for the synthesis of modified pharmaceutical peptides and proteins with enhanced biological properties [1] . However, their synthesis remains challenging and underdeveloped [11g, 22] . Encouraged by the good results obtained for aryl and alkyl α‐keto amides, we wondered whether this strategy could be extended to β‐branched α‐keto amides to afford enantioenriched β‐branched α‐amino amides via a DKR process [23] .…”
Section: Resultsmentioning
confidence: 99%
“…Enantiopure β‐branched α‐amino acids are very important molecules for the synthesis of modified pharmaceutical peptides and proteins with enhanced biological properties [1] . However, their synthesis remains challenging and underdeveloped [11g, 22] . Encouraged by the good results obtained for aryl and alkyl α‐keto amides, we wondered whether this strategy could be extended to β‐branched α‐keto amides to afford enantioenriched β‐branched α‐amino amides via a DKR process [23] .…”
Section: Resultsmentioning
confidence: 99%
“…[162] Wang et al have been committed to the regioselective and enantioselective synthesis of non-protein α-amino acid series. [163] Based on the guidance of previous work, [164] in 2021, they successfully reported that the enantiomeric radial coupling reaction between glycine ester and racemic α-bromoketone of the photo-redox dual catalytic system was used to synthesize enantiomer-rich α-amino acid derivatives (Scheme 44).…”
Section: Combining Brønsted Acid Catalysis With Photoredox Catalysismentioning
confidence: 99%
“…in 2021 (Scheme 84). [154] This radical cross‐coupling process generated two chiral centers and featured high enantioselectivity and good diastereoselectivity. A wide range of racemic α‐bromoketones and glycine esters were well tolerated and generated α ‐amino acid derivatives in 51–89 % and 68–99 % ee with 1.2 : 1 to >20 : 1 dr.…”
Section: Photoredox/chiral Brønsted Acid/base Dual Catalysismentioning
confidence: 99%
“…No reaction occurred when propiophenone and N ‐phenyl glycine imino ester were treated under standard conditions, which excluded the Mannich‐type two‐electron pathway. Accordingly, the authors proposed that photoexcited catalyst *Ir III (* E 1/2 *III/II =+1.21 V vs. SCE) [14] oxidizes the glycine ester ( 85.1 , E 1/2 ox =+0.95 V vs. SCE), [154] followed by deprotonation and 1,2‐H shift to afford α ‐amino radical 85.3 and Ir II ( E 1/2 III/II =−1.37 V vs. SCE) [14] as strong reducing species (Scheme 85). This species then reduces α‐bromoketones 85.2 to produce radical intermediate 85.4 and regenerate Ir III photocatalyst.…”
Section: Photoredox/chiral Brønsted Acid/base Dual Catalysismentioning
confidence: 99%